Answer:
2KClO3(s) → 2KCl(s) + 3O2(g)
Explanation:
Step 1: Data given
Solid potassium chlorate = KClO3(s)
solid potassium chloride = KCl
oxygen gas = O2
Step 2: The balanced equation
KClO3(s) → KCl + O2
On the left side we have 3x O, on the right side we have 2x O
To balance the amount of O we have to multiply KClO3 (on the left side) by 2 and multiply O2 on the right side by 3
2KClO3(s) → KCl(s) + 3O2(g)
On the left we have 2x K, on the right we have 1x K.
To balanced the amount of K we have to multiply KCl on the right side by 2
Now the equation is balanced
2KClO3(s) → 2KCl(s) + 3O2(g)